Every song ever : twenty ways to listen in an age of musical plenty - Ratliff, Ben (New York : Farrar, Straus and Giroux, 2016)
What is music in the age of the cloud? Today, we can listen to nearly anything, at any time. It is possible to flit instantly across genres and generations, from 1980s Detroit techno to 1890s Viennese neo-romanticism. This new age of listening brings with it astonishing new possibilities--as well as dangers. --Publisher.
What does it mean to listen in the digital era? Today, new technologies make it possible to roam instantly and experimentally across musical languages and generations, from Detroit techno to jam bands to baroque opera--or to dive deeper into the set of tastes that we already have. Either way, we can listen to nearly anything, at any time. The possibilities in this new age of listening overturn old assumptions about what it means to properly appreciate music--to be an "educated" listener. Here, veteran music critic Ben Ratliff reimagines the very idea of music appreciation for our times. As familiar subdivisions like "rock" and "jazz" matter less and less and music's accessible past becomes longer and broader, listeners can put aside the intentions of composers and musicians and engage music afresh, on their own terms. Ratliff isolates signal musical traits--such as repetition, speed, and virtuosity--and traces them across wildly diverse recordings to reveal unexpected connections. When we listen for slowness, for instance, we may detect surprising affinities between the drone metal of Sunn O))), the mixtape manipulations of DJ Screw, Sarah Vaughan singing "Lover Man," and the final works of Shostakovich. And if we listen for closeness, we might notice how the tight harmonies of bluegrass vocals illuminate the virtuosic synchrony of John Coltrane's quartet. Ratliff also goes in search of "the perfect moment"; considers what it means to hear emotion; and examines the meaning of certain common behaviors, such as the impulse to document and possess the entire performance history of the Grateful Dead. Encompassing the sounds of five continents and several centuries, Ratliff's book is an artful work of criticism and a lesson in open-mindedness. It is a definitive field guide to our radically altered musical habitat.--Adapted from dust jacket.
Let me concentrate! : repetitition -- Past present future : slowness -- Draft me! : speed -- What if we both should want more? : transmission -- We don't need no music : quiet/silence/intimacy -- Church bell tone : stubbornness and the single note -- Elevation : virtuosity -- Blue rules : sadness -- Getting clear : audio space -- Purple, green, turquoise : endless inventory -- I forgot more than you'll ever know : wasteful authority -- Granite and fog : density -- As it first looks : improvisation -- Eyeball to eyeball : closeness -- Just a little bit : loudness -- R.S.V.P. : discrepancy -- I still believe I hear : memory and historical truth -- On the waves : linking -- Mi gente : community and exclusivity -- Slowly fading out of sight : the perfect moment.
Each chapter followed by a suggested listening list.
Includes bibliographical references (pages 237-239) and index.
Keywords: Music appreciation; Music -- Psychological aspects; Music appreciation; Music -- Psychological aspects